STRATEGI SUSTAINABILITAS PEMBIAYAAN BAITUL MAAL WAT TAMWIL (BMT) DI KOTA PADANG - Nofri Yendra, Mohammad Abdilla (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
This study aims to identify the determinants of the sustainability of Baitul Maal Tamwil(BMT) as Sharia Microfinance Institutions (LKMS) which are problematic in managing existingrisks so as to disrupt the sustainability of BMT institutions. The research method consists of thepre-research stage, data collection stage, data processing stage and interpretation of results. Theresearch location in Padang City BMT, West Sumatra Province, is spread in 11 districts. Theresearch population of all BMTs in the city of Padang in West Sumatra province was 104 units andthe sample was taken in total sampling of 104 participants. The independent variable of theresearcher consists of the aspects of regulation, supervision, infrastructure, human resources andproduct innovation while the dependent variable of BMT sustainability is measured by assetgrowth, financing quality and profitability collected using a questionnaire. The research modeluses multiple linear regression and hypothesis testing partially and simultaneously at α = 5%. Theresults of the partial hypothesis testing are only product innovations that affect the sustainability ofthe financing of BMT in Padang City, West Sumatra Province. The results of simultaneoushypothesis testing show that all independent variables have an effect on the sustainability of theBMT financing in West Sumatra Province. This can also be seen based on the correlationcoefficient value of 40.1% (classified as weak) and the Adjusted R Square value of 11.8%.The results of the strategy factor analysis in the form of Weakness - Opportunities producesthe following 5 strategies: 1) developing linkage programs with sharia financial and bankinginstitutions to obtain low-cost funds, 2) adding marketing personnel who are able to manage andplace funds, 3) improve the risk management oversight function in operational activities throughimprovement of the Operations Management Standards and Standard Operating Procedures, theestablishment of the Sharia Management Board, improvement in handling problematic financingand re-empowering committees established in the organizational structure, 4) improving servicesto members, customers and the community through improved facilities and infrastructure,especially information technology services which can reach and meet the needs of members andcustomers, providing services products that are cheap and fast but still in accordance with shariaprinciples and provide services for the collection and distribution of zakat, infaq, shodaqah andwaqf, 5) improving elementary competence through training and coaching as well asperformance-based awards to focus on business development according to sharia principles.Keywords: sustainability, regulation, supervision, infrastructure, human resources and productinnovation